2019
DOI: 10.3390/mi10040226
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Injection Speed on Oocyte Deformation in ICSI

Abstract: Oocyte deformation during injection is a major cause of potential cell damage which can lead to failure in the Intracytoplasmic Sperm Injection (ICSI) operation used as an infertility treatment. Injection speed plays an important role in the deformation creation. In this paper the effect of different speeds on deformation of zebrafish embryos is studied using a specially designed experimental set-up. An analytical model is developed in order to link injection force, deformation, and injection speed. A finite e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…As the algorithm had been validated, it was then used to evaluate the effect of egg-injection parameters such as speed on the vibration. In the previous publication, the authors demonstrated the variations in forces and deformation creation during egg injection [8]. In this research, the potential contribution of the demonstrated factors is evaluated in vibration creation which may be a cause of egg damage during the penetration.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…As the algorithm had been validated, it was then used to evaluate the effect of egg-injection parameters such as speed on the vibration. In the previous publication, the authors demonstrated the variations in forces and deformation creation during egg injection [8]. In this research, the potential contribution of the demonstrated factors is evaluated in vibration creation which may be a cause of egg damage during the penetration.…”
Section: Resultsmentioning
confidence: 94%
“…Injection speed and trajectory of the injection pipette are two main injection parameters that contribute toward a successful egg injection [6]. The displacement of the injection pipette is affected significantly by cell injection speed and its trajectory [7,8]. Besides, the magnitude of the vibration at the tip of the injection pipette increases since the injection procedure requires acceleration and deceleration of the injection pipette [9].…”
Section: Introductionmentioning
confidence: 99%
“…Oocyte morphological assessment is the most widely used method in clinical practice; a normal human MII oocyte should have a round and clear ZP, a small PVS containing a single IPB without fragmentation and pale, moderately granular cytoplasm with no inclusions ( 18 ). However, oocyte morphological assessment may be performed only after oocyte denudation in ICSI cases and potential mechanisms that change the appearance of the oocyte are multifactorial ( 19 ). Age and the E 2 level on the HCG day are indirect indicators ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, an optimum range of injection speeds has to be determined. An automated system should be able to determine the speed and force of injection based on the biophysical properties of the oocyte (103).…”
Section: Oocytesmentioning
confidence: 99%